2002
DOI: 10.1007/s001980200087
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonates in the Treatment of Thalassemia-Induced Osteoporosis

Abstract: The aim of our randomized, placebo-controlled study was to investigate the effects of 2 years' daily oral administration of alendronate or intramuscular administration of clodronate every 10 days, on bone remodeling parameters and bone mineral density (BMD), safety and tolerability in a group of osteoporotic thalassemic patients. Twenty-five young patients (mean age 26.6 +/- 7.1 years) with beta-thalassemia major were randomly divided to receive placebo or 100 mg of clodronate intramuscularly every 10 days or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
11

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 36 publications
1
42
0
11
Order By: Relevance
“…However, despite improved treatment for this hematologic disorder and its complications, TM patients exhibit unbalanced bone turnover, with increased bone resorption and decreased bone formation resulting in diminished bone mineral density (BMD) [7][8][9][10]. The RANK/RANK-L/OPG system has been recognized as a major regulator of osteoclast proliferation and activation, and its role has also been described in the pathogenesis of TM-induced osteoporosis Abstract Subjects affected by thalassemia major (TM) often have reduced bone mass and increased fracture risk.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite improved treatment for this hematologic disorder and its complications, TM patients exhibit unbalanced bone turnover, with increased bone resorption and decreased bone formation resulting in diminished bone mineral density (BMD) [7][8][9][10]. The RANK/RANK-L/OPG system has been recognized as a major regulator of osteoclast proliferation and activation, and its role has also been described in the pathogenesis of TM-induced osteoporosis Abstract Subjects affected by thalassemia major (TM) often have reduced bone mass and increased fracture risk.…”
Section: Introductionmentioning
confidence: 99%
“…Una bassa DMO è associata, nei T, alla cardiomiopatia, al diabete, all'epatite cronica, all'incremento delle transaminasi, all'amenorrea (31) ed alla mancata terapia ormonale sostitutiva nei casi di ipogonadismo ipogonadotropo (29)(30)(31). A carico del tessuto osseo, in corso di ST si determina: -basso valore del rapporto osteoprotegerina (OPG)/ RANKL con (a) livelli di OPG sovrapponibili (39) o diminuiti (40,41) e (b) netto aumento del RANKL rispetto alla popolazione generale (39); -alti livelli di cross-links del piridinio e di N-telopeptidi urinari (39,(41)(42)(43); -livelli diminuiti di osteocalcina, fosfatasi alcalina ossea e C telopeptide del procollagene I (40, 43); -riduzione della attività osteoblastica a causa dei depositi di ferro (44); -ridotta 25-idrossilazione della vitamina D a causa della emosiderosi epatica e della possibile presenza di epatite post-trasfusionale (33, 34); -ridotta secrezione di GH con conseguente ridotta proliferazione degli OB (9, 45) e, da parte di questi ultimi, ridotta secrezione di insulinlike growth factor I (IGF-I) (39) e di Insulin-like growth factor binding protein-3 (IGFBP-3) (29); -correlazione statisticamente significativa dei diminuiti livelli di IGF-I con la diminuizione della DMO (41); -correlazione inversa tra l'aumento del RANKL ed i livelli di testosterone libero e 17-b-estradiolo (39).…”
unclassified
“…Additional studies found that osteopenia and osteoporosis are emerging as important causes of morbidity in patients of both genders with thalassemia [14,19,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%